The role of federalism in mitigating ethnic conflicts in plural societies : Nigeria and Malaysia in comparative perspective / Chukwunenye Clifford Njoku - Njoku, Chukwunenye Clifford (2015)
This study examines the challenges of ethnic conflict in Nigeria and Malaysian plural societies, in view of the demands their diverse ethnic groups impose on nation-building. This tension is largely exacerbated by factors that favour group dominance particularly on the right to resources which mostly fractures effort at achieving national cohesion. This study is important given the persistent problem of instability which has affected the development and well-being in both countries. The ethnic problem in Nigeria is centered on two polar extremes - the Government position that “Nigeria’s unity is not negotiable and must not be discussed” in its lopsided nation-building posture, and some ethnic groups that see themselves as viable nations entrapped in an invented nation-state. This thesis discusses reoccurring problems that have bedeviled Nigeria as a nation since its independence in 1960 as observed in continuing ethnic conflicts, which are less mitigated due to its fledging federalism which ought to have enhanced interethnic harmony within its multi-ethnic society. The thesis highlights ethnic demands resulting in militancy over “Resource Control”, “Religious Intolerance” as well as “Secessionist Movements” in the face of persistent inequality and unfairness to some ethnic groups in Nigeria. This may explain disunity in Nigeria. These are some of the contested issues that have fractured efforts at achieving smooth nation-building and national development. This is the focus of the thesis, which provides a lens to view Malaysia’s achievement in its interethnic harmony, political stability and social development. However, investigation reveals how leadership role and policy implementation over decades in Malaysia have led to good wealth distribution although with inherent institutionalised preferential policies in favour of its Malay ethnic majority as a solace against tension. It explains Malaysia’s ethnicised federal practice which is uncommon that largely constitutes huge ethnic tensions beneath the surface in the country as observed in its grumbling minority groups while the system has remained considerably and progressively stable. Hence this work reconciles the problem in Nigeria within the embrace of progress made by Malaysia whose similar society has lived a relatively peaceful life for over half a century. Inequality, denial and social exclusion, inept leadership as well as institutional inadequacy are found to have exacerbated ethnic conflicts in Nigeria hence the state totters in the face of tension. This study is a mirror to view construction and reconstruction in Nigeria’s sociopolitical space which defines its continuity and discontinuity, while it aligns Nigeria to Malaysia’s success in interethnic balance. Given this insight, the thesis argues that no multiethnic nation-state makes substantial social progress or survives outside the axis of its interethnic balance. This is Nigeria’s challenge in nation-building. Significantly, the study relies on empirical evidence as well as secondary data while providing logic for comparison. Relatively, theory of federalism is adopted in this study as conflict mitigating mechanism in plural societies to clarify different issues in both countries while the thesis concludes with relevant recommendations.